Good Governance and Good Public Administration - Patyi, András (Public Governance, Administration and Finances Law Review, 2016)
The following article will examine the main principles of good governance and good public administration. It will outline the structure of reforms which have been accomplished in Hungary since the change in government in 2010, with special attention paid to the provisions of the new Constitution of Hungary that entered into force in 2012, and the Magyary Zoltán Public Administration Development Program, which will elaborate on the characteristics of what is considered the ‘good state.’